Firm-Specific Worker Incentives, Employee Retention, and Wage–Tenure Slopes - Kryscynski, David (Organization Science, 2021)
Strategy scholars have long studied the strategic implications of firm-specific human capital but have almost completely ignored their conceptual dual: firm-specific worker incentives. This paper proposes that firm-level incentives can also vary in firm specificity, and accordingly, firm-specific incentives may help to explain advantages independent of the firm specificity of human capital. Results from a proprietary data set, including data from 284 software development firms and matched employee-level compensation data for 8,208 software developers in 99 of those firms, suggest that firms with higher firm specificity in their incentive bundles may have lower dysfunctional employee turnover rates as well as lower wage–tenure slopes. In other words, these firms may lose fewer employees who they would prefer to keep and may be able to do so while still offering lower wage increases over time than their competitors in the labor market. Thus, firm-specific incentives may provide a viable alternative pathway to human capital–based competitive advantages.